Laboratory Manual in Food Safety and Sanitation - Ang, Mary Jean C.; Balanon, Hannah A. (Quezon City, 2010)
A practical laboratory manual focusing on essential food safety and sanitation principles, designed to guide students in maintaining hygienic practices and ensuring safe food handling in various settings.
Keywords: Food - Saftey Measures; Food - Storage; Food handling - Safety Measures